The reality of school crises management in public schools in capital city of sana'a, Republic of Yemen - Abdalwahab, Amal Mahfoud Khaled (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the reality of crisis management in public schools in Sana'a, the capital city of the Republic of Yemen. The researcher used a descriptive survey approach and designed a questionnaire that was administered to a sample of 650 principals, deputy principals, and teachers. The study found that the reality of crisis management in public schools in Sana'a was highly positive in all domains- namely the effectiveness of crisis management, recovery of activity, crisis response, education and evaluation, early warning, preparedness and prevention. The findings also revealed statistically significant differences at the significance level of (0.05 ≥ α) in the responses of the participants regarding the reality of crisis management in public schools in Sana'a, which was ascribed to the variables of gender- mainly males- and job title, particularly principals. No such differences are attributed to the the variables of educational area and the frequency of participation.Accordingly, the study came up with numerous recommendations, including the following: -It is necessary that senior educational leadership in the Ministry of Education pays special attention to the phases of crisis management, especially the early warning phase through which educational leaders can predict future variables in education management. It is also recommended that an emergency room (crisis management team) be established in the Education Department, and all its needs be met to conduct its work as required and attain the desired goals.
Keywords: Crisis management; public education; Sana'a; Republic of Yemen